Students clean up community hall, donate fans - Borneo Post, (KK) (Borneo Post (KK), 2013)
PENAMPANG: Twenty-four distant learning students from Universiti Utara Malaysia (UUM) participated in a community service at Kampung Sugud near here yesterday. Representing the students, Juvina Jimis told reporters that among the activities they had carried out at the village were to clean up the Kampung Sugud Community Hall.